Konsep dan Implementasi Corporate Social Responsibility (CSR) dalam Bisnis: Studi Literatur - Nabila Kumala Wijayanti; Ulfa Adiranti; Amelia Siti Ariyanti; Mohamad Djasuli (Jurnal Mirai Management, 2023)
Introduction/Main Objectives: Corporate Social Responsibility (CSR) is a concept characterized by three main dimensions: voluntary action, philanthropy, and obligation. It reflects a company's responsibility towards society, the environment, and the economy. Background Problems: The increasing importance of CSR in contemporary business environments raises questions about its evolution and application. As businesses navigate complex social, environmental, and economic landscapes, understanding the dynamics of CSR becomes crucial. This study addresses the need for an updated exploration of CSR literature to capture recent developments and insights. Novelty: This research contributes to the existing body of knowledge by providing a comprehensive review of CSR literature post-2000. By utilizing the PRISMA 2009 guidelines, the study ensures a systematic and transparent approach to literature selection, offering a nuanced understanding of the various aspects of CSR. The novelty lies in synthesizing diverse perspectives on CSR, including definitions, approaches, strategies, benefits, challenges, and indicators. Research Methods: The research employs a literature review methodology, guided by the PRISMA 2009 framework. The researcher systematically searches for relevant literature on CSR using specific keywords across multiple databases. Finding/Results: The literature review reveals a wealth of information on CSR, covering diverse aspects such as its definitions, various approaches adopted by businesses, strategies for implementation, perceived benefits, existing challenges, and measurable indicators. The findings offer a panoramic view of the evolving landscape of CSR, highlighting global perspectives and trends. Conclusion: In conclusion, this study provides a holistic understanding of the concept and implementation of CSR in the global context. The synthesis of literature post-2000 sheds light on the multifaceted nature of CSR, emphasizing its voluntary, philanthropic, and obligatory dimensions. The study underscores the significance of CSR in shaping corporate behavior and contributing to societal, environmental, and economic well-being. The insights gained from this research can inform businesses, policymakers, and scholars about the current state of CSR and potential future directions. Keywords: Corporate Social Responsibility (CSR), literature review, CSR concept, CSR implementation.